2004
DOI: 10.1016/j.gloplacha.2003.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Glacier ice mass fluctuations and fault instability in tectonically active Southern Alaska

Abstract: Across southern Alaska the northwest directed subduction of the Pacific plate is accompanied by accretion of the Yakutat terrane to continental Alaska. This has led to high tectonic strain rates and dramatic topographic relief of more than 5000 meters within 15 km of the Gulf of Alaska coast. The glaciers of this area are extensive and include large glaciers undergoing wastage (glacier retreat and thinning) and surges. The large glacier ice mass changes perturb the tectonic rate of deformation at a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 43 publications
5
44
2
Order By: Relevance
“…We did not expect that in 1985-1999 the melting area of ice mass to be almost equal compared with ice mass melting during 1999-2013. The retreat of all three GLs in the same period, without earthquakes and landslides (Sauber and Molnia, 2003), help us understand that the main factor contributing to the melting is climate change (Oerlemans, 1994;Haeberli et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not expect that in 1985-1999 the melting area of ice mass to be almost equal compared with ice mass melting during 1999-2013. The retreat of all three GLs in the same period, without earthquakes and landslides (Sauber and Molnia, 2003), help us understand that the main factor contributing to the melting is climate change (Oerlemans, 1994;Haeberli et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Surface displacement and ice mass fluctuation were demonstrated by GLs from South Alaska related to earthquakes and active tectonics (Sauber and Molnia, 2003). The landslides and thick debris cover triggered by earthquakes can significantly change the ablation rate of GLs (Post, 1967;Krimmel and Meier, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Questions remain, however, most particularly in relation to the time scales over which a geospheric response may be detectable. Although increases in the incidence of climate-change-driven, large-volume rock and ice avalanches (Huggel et al 2008(Huggel et al , 2010Huggel 2009), and the suggested modulation of seismicity in areas of large-scale ice wastage (Sauber & Molnia 2004;Sauber & Ruppert 2008), lead to speculation that climate change is already drawing out a crustal response, no increase in the global incidence of either volcanic activity or seismicity has been identified to date, nor has any change in the stability of submarine slopes been detected. It may be the case that modulation of potentially hazardous geological and geomorphological processes due to anthropogenic climate change proves to be too small a signal to extract from the background noise of 'normal' geophysical activity, at least in the short to medium term.…”
Section: Discussionmentioning
confidence: 99%
“…Glacier mass fluctuations in south central Alaska have been charged with modulating the recent seismic record, and even implicated in the triggering of the 1979 magnitude 7.2 St Elias earthquake Sauber & Molnia 2004;Sauber & Ruppert 2008). Rapid ice-mass loss at the many glaciated volcanoes in Alaska and Kamchatka, driven by surface temperature rises that could exceed 15…”
Section: (A) High-latitude Regionsmentioning
confidence: 99%
“…Although some studies have been carried out in this region since 1999 (Pavlis and others, 2004), it is not possible at this time to construct a better model of the faulting, and the model assumed is that used in the 1999 map. As a proxy for a more detailed understanding, a flat fault surface (that is, with a 0° dip) at a depth of 15 km was assumed, extending from 59.1° to 61.0° N. and from 139.5° to 145.4° W. This is nearly identical to the dislocation model proposed by others (1997, 1998; see also Sauber and Molnia, 2004) to explain GPS observations in this region. Sauber and others (1997) estimate that sufficient strain has accumulated in this region since 1899 to generate an earthquake of magnitude Mw 8.1.…”
Section: Yakataga Regionmentioning
confidence: 91%